A Review on Inclusion of Agriculture Subject in the High Schools of Bhutan: Perspective and Challenges - Ugyen; Sonam Rinchen (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Inclusion of Agriculture subject in the curriculum plays a very vital role in the country where the economic is fully dependent on agriculture. Agriculture education provides an alternative to career ladder for those students who are interested in taking farming in the future. In Bhutan inclusion of Agricultural subject became a part of school’s curriculum under the joint initiative of Agriculture and Education ministry from 2013 onwards. Agriculture inclusion in the curriculum of the school brings both the perspective and the challenges to the learners and also to the teachers. The main aim of introducing the curriculum is to make children learn through practical teaching and prepare them to value the dignity of work. But there are also many challenges faced by the student during the learning period that demotivates the children in opting agriculture as their vocational subject. This study aims to find out the challenges encountered by the students of IX-XII in taking up the optional Agricultural subject and also explore some of the benefit gained by the students in taking it to make it worthy in taking up their optional subjects.